Buying and Running a Small Hotel : The Complete Guide to Setting Up and Managing Your Own Hotel, Guest House or B & B - Parker, Ken, 1934- (Oxford How To Books, 2005)
Deciding whether hotel-keeping is for you; 2. Choosing the right hotel for you; 3. Making the search; 4. Raising capital; 5. Making your purchase; 6. Assessing equipment and staffing; 7. Book-keeping and accounts; 8. Tariffs, costs and advertising; 9. Up and running
Include Illustrations, Appendix, Glossary and Index
Keywords: Hotel management